Non‐invasive detection of bladder cancer via expression‐targeted gene delivery. (28th November 2017) - Fang, Yunlan; Wolfson, Benjamin; Godbey, W T.
Abstract: Background: Because of the time and expense associated with the procedures and possible distress to the patient, cystoscopy or other imaging techniques are typically not used for bladder cancer detection before symptoms become present. Alternatively, commercial assays for urinary tumor markers exist but are marred by low sensitivity and high cost. There is a need for a simple and sensitive means of tumor detection, such as via the analysis of urine. Methods: Plasmids encoding the secretable reporter Gaussia Luciferase (G.LUC), under the control of cmv, cox2 or opn promoters, were delivered via polyethylenimine into bladder tumor cells in culture and into the bladders of mice. Expression profiles of the reporter were recorded, the optimal times for reporter detection were determined and the relationship of reporter expression with tumor size was calculated. Results: In vitro results showed that both the cox2 and opn promoters can drive significant expression of G.LUC in bladder carcinoma cells in a targeted fashion. In vivo results demonstrated that the cox2 promoter caused expression of G.LUC at detectable levels in the urine, with local signal maxima occurring at 48 and 72 h post‐transfection. G.LUC levels in the urine had a 24‐h periodicity, with the periodicity partly being the result of an agent secreted by tumor cells that served to mask the luciferase signal. Conclusions: Having shown tumor specificity and having been calibrated with respect to circadian expression patterns, the detection system shows great promise for future investigation of tumor presence both in the urinary bladder and other models of cancer.